Examen especial y ajustes al componente vehículos de la empresa Estudiar S.A en el año 2017. - Morocho Moran, Samanta Katiusca (My University, 2019)
The present investigation, is oriented to conceptualize and analyze the planning and application of the special examination with the respective adjustments of the vehicles account of the Company Study S.A. to the 2017 period; For this, the stages of an audit and the planning of the special examination were defined. Therefore, it is stressed that the success of everything is given under the International Auditing Standards related to the responsibilities of the auditor against planning and evidence. For the development of the present case, the non-experimental and bibliographical descriptive methodology was used; that is, information was selected from various sources such as books and scientific journals allowing to be analyzed, detailed to arrive at reasonable optimal results. It is important to emphasize that every company requires internal control of their accounts, especially Property, Plant and Equipment; since it will induce to detect irregularities of risks such as improper calculations, inadequate application of percentages of depreciation, and other adjustments that need to be made; it is there, where the special examination must be done through the audit that will allow management to identify problems in order to minimize risks and make efficient decisions. Therefore, when audit findings and poor accounting procedures are found, adjustments are made in the Vehicle category, which directly affects the year's Profit, income tax, depreciation expenses and the accumulated depreciation of both the Balance Sheet as Comprehensive Results States.
La presente investigación, está orientada a conceptualizar y analizar la planificación y aplicación del examen especial con los respectivos ajustes de la cuenta vehículos de la Empresa Estudiar S.A. al periodo 2017; para ello se definió las etapas de una auditoria y, la planificación del examen especial. Por lo tanto, se recalca que el éxito de todo se encuentran dado bajo las Normas Internacionales de Auditoria relacionadas a las responsabilidades del auditor frente a la planificación y a las evidencias. Para el desarrollo del presente caso, se utilizó la metodología descriptiva no experimental y bibliográfica; es decir, se seleccionó la información de diversas fuentes como libros y revistas científicas permitiendo ser analizadas y detalladas para llegar a resultados óptimos razonables. Es importante hacer énfasis que toda empresa requiere hacer control interno de sus cuentas especialmente el de Propiedades, Planta y Equipo; ya que inducirá a detectar irregularidades de riesgos como cálculos indebidos, aplicación inadecuados de porcentajes de depreciación, y otros ajustes que se necesiten realizar; es ahí, en donde se debe hacer uso del examen especial mediante la auditoria que permitirá orientar a la gerencia en la identificación de problemas con la finalidad de minimizar riesgos y tomar decisiones. Por ende, cuando se encuentran hallazgos de auditoria y deficientes procedimientos contables se procede a realizar ajustes en el rubro de Vehículos lo que afecta directamente el Resultado del ejercicio, impuesto a la renta, gastos de depreciación y la depreciación acumulada tanto del Balance General como Estados de Resultados integrales.
Keywords: CONTROL INTERNO; PLANIFICACIÓN; EXAMEN ESPECIAL; PROPIEDADES; PLANTA Y EQUIPO; DEPRECIACIÓN